THE ESTABLISHMENT OF ONE HIGH COURT FOR MALAYSIA: A PIPE DREAM OR A POSSIBILITY? - Sheila Ramalingam,; Dato’ Johan Shamsuddin Sabaruddin,; Saroja Dhanapal, (Journal of Malaysian and Comparative Law, 2025)
On 9 July 1963, the Malaysia Agreement was signed in London for the formation of Malaysia, which would consist of among others, the Federation of Malaya, Sabah and Sarawak. Malaysia officially came into being as a sovereign nation on 16 September 1963. The 1957 Federal Constitution (which hitherto only applied to the Federation of Malaya) was then extensively amended to make it into a Federal Constitution for Malaysia. However, many aspects of the judicial and legal system as it was before the formation of Malaysia were maintained, as a compromise for the states of Sabah and Sarawak to join Malaya and become the Federation of Malaysia. On the advent of the formation of Malaysia, the Cobbold Commission was of the view that due to the distance between West and East Malaysia, there should be a separate High Court in the Borneo territories presided over by its own Chief Justice, with appeals going to a Federal Supreme Court for the whole of Malaysia. The two High Courts in Malaysia have remained in place until now, almost 60 years later. This paper seeks to explore whether there is still a need for there to be two High Courts in Malaysia, and whether there is at least the possibility of establishing a single High Court for the whole of Malaysia in place of the current two High Courts of co-ordinate jurisdiction and status in Malaysia.